Expression of Beclin-1 and Caspase-3 After the Myocardial Contusion in Rats With High and Low Stress Resistance - E. I. Klyuchnikova; O. V. Korpacheva; S. I. Mozgovoi; A. N. Zolotov; A. V. Kononov (Фундаментальная и клиническая медицина)
Aim. To evaluate the activity of autophagy and apoptosis in the myocardium of rats with differentstress resistance after the modeling of myocardial contusion.Materials and Methods. The study was performed on 106 white male rats weighing 250-300 g. The rats were ranked according to stress tolerance, and medium-resistant individuals (n = 42) were excluded from the experiment. Control (n = 16) and experimental (n = 48) groups were formed from the remaining animals; the control group included subgroups with high and low stress resistance, and the experimental group included 6 subgroups (rats with high and low stress resistance; 6, 12, and 24-hour time points). Each of the subgroups included 8 animals. Myocardial contusion was modeled in the experimental group. At 6-, 12- and 24-hour time point, rat hearts have been excised and 5×5 mm myocardial fragments were dissected from the areas with the most prominent traumatic effects (interventricular septum, anterior walls of the left and right ventricles). Tissues were then sectioned and stained with antibodies to Beclin-1 and caspase-3.Results. We have documented a significant expression of Beclin-1 and Caspase 3 expression in rat hearts after myocardial contusion. From 6 to 24 hours upon the myocardial contusion, Beclin-1 expression has been increased in rats with high stress resistance but was reduced in rats with low stress resistance. Expression of caspase-3 expression was registered exclusively at 24-hour time point in rats with high stress resistant but increased along the time points in rats with low stress resistance.Conclusion. Expression of Beclin-1 and caspase-3 in rat myocardium indicated autophagy and apoptosis upon the myocardial contusion. Temporal patterns of Beclin-1 and caspase-3 expression were opposite in rats with high and low stress resistance.